Application of SNAP-Tag in Expansion Super-Resolution Microscopy Using DNA Oligostrands - Yao, Longfang; Zhang, Li; Fei, Yiyan; Chen, Liwen; Mi, Lan; Ma, Jiong (Frontiers in Chemistry, 2021)
Expansion super-resolution technology is a new technology developed in recent years. It anchors the dye on the hydrogel and the dye expands with the expansion of the hydrogel so that a super-resolution map can be obtained under an ordinary microscope. However, by labeling the target protein with a first antibody and secondary antibody, the distance between the fluorescent group and the actual target protein is greatly increased. Although fluorescent proteins can also be used for expansion super-resolution to reduce this effect, the fluorescent protein is often destroyed during sample preparation. To solve this problem, we developed a novel label system for expansion microscopy based on a DNA oligostrand linked with a fluorescent dye, acrylamide group (linker), and benzoylguanine (BG, a small substrate molecule for SNAP-tag). This protocol greatly reduced the error between the position of fluorescent group and the actual target protein and also reduced loss of the fluorescent group during sample preparation.